2020
DOI: 10.1039/c9en01303b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient ammonia recovery from wastewater using electrically conducting gas stripping membranes

Abstract: Recovery of nutrients, such as ammonia, from wastewater offers an attractive approach to increase the overall sustainability of waste management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 76 publications
1
30
1
Order By: Relevance
“…22 Slightly lower NH 3 recovery rates were produced in our study compared to the other previous study (68.8 ± 8.0 gNH 3 -N/m 2 /d) where a Ni-CNT/PTFE membrane electrode was examined. 23 However, in that study, a different cell configuration was used to primarily separate aqueous NH 4 + from synthetic wastewater across a cation exchange membrane using an electric field. Indirect NH 3 -N recovery from synthetic wastewater with fewer hindrances might have resulted in such high NH 3 recovery fluxes with low energy consumptions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Slightly lower NH 3 recovery rates were produced in our study compared to the other previous study (68.8 ± 8.0 gNH 3 -N/m 2 /d) where a Ni-CNT/PTFE membrane electrode was examined. 23 However, in that study, a different cell configuration was used to primarily separate aqueous NH 4 + from synthetic wastewater across a cation exchange membrane using an electric field. Indirect NH 3 -N recovery from synthetic wastewater with fewer hindrances might have resulted in such high NH 3 recovery fluxes with low energy consumptions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The other study reported NH 3 fluxes of 68.8 ± 8.0 gNH 3 -N/m 2 /d using a Ni-CNT/ polytetrafluoroethylene (PTFE) membrane electrode in a twochamber cell separated by a cation exchange membrane to selectively harvest NH 4 + from synthetic wastewater. 23 However, the practical application of carbon nanomaterials in the membrane electrode for NH 3 recovery is still uncertain due to the difficulties of large-scale production. 24 In this study, we examined a Ni-functionalized activated carbon (AC) electrode with a hydrophobic layer formed by a simple phase inversion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrophobic or electrically conducting membranes have been recently developed to efficiently recover (or capture) valuable resources, such as ammonia and phosphate, from wastewater [ 103 , 104 ]. These membranes facilitate the conversion of ammonium into ammonia or enhance the mass transfer of the target compound.…”
Section: Energy and Resource Recoverymentioning
confidence: 99%
“…Thus, a large amount of ammonia still remains in the solution after struvite precipitation, resulting in a low rate of overall ammonia recovery and requiring further targeted recovery of ammonia. Various technologies, including air stripping, forward osmosis, ion exchange, and electrodialysis, have been evaluated to recover ammonia from wastewaters. , Among these technologies, air stripping is highly effective in ammonia recovery from HT process water. , Especially, prior studies showed high N and P recovery efficiencies for urine via employing the combined processes of air stripping and struvite precipitation. , Thus, we hypothesize that a sequential struvite precipitation and air stripping process can maximize P and N recovery from HT process water, as the pH range (8–10) for struvite precipitation can be adjusted to facilitate downstream ammonia recovery through air stripping (the p K a value of NH 3 is 9.25) . Given that the presence of Fe inhibits formation of struvite precipitates, it is important to evaluate this sequential process for P/N recovery from HT process water derived from Fe-rich sludges.…”
Section: Introductionmentioning
confidence: 99%